2009
DOI: 10.2478/v10003-009-0007-3
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Carbon-14 and Tritium For Peat and Water Dynamics Characterization: Case of Čepkeliai Peatland, Southeastern Lithuania

Abstract: Abstract:The present investigation conducted in Čepkeliai peatland (south-eastern Lithuania) deals with two radioisotope methods -carbon-14 ( 14 C) and tritium ( 3 H).14 C was applied to peatland chronology and sedimentation rate estimation and 3 H to peat water dynamics characterization. According to 14 C data, peatland development began since 12650-11350 years cal BP and peat accumulation since 10550-9700 years cal BP with peat accumulation rate of 0.27-0.79 mm/year in the central part of the peatland. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…as discussed by Western et al, 2009). Using 3 H activities, transit times of years to decades were proposed for water from metre-to tens-of-metres-thick peat deposits in Quebec, Canada (Dever et al, 1984), Dartmoor, UK (Charman et al, 1999), Lithuania (Mažeika et al, 2009), and Minnesota, USA (Siegel et al, 2001). From the preservation of seasonal δ 18 O and δ 2 H values, Aravena and Warner (1992) estimated that the water from the upper ∼ 0.1 m of peat from Ontario, Canada, was < 1 year old.…”
Section: Transit Times In Upland Peatmentioning
confidence: 99%
“…as discussed by Western et al, 2009). Using 3 H activities, transit times of years to decades were proposed for water from metre-to tens-of-metres-thick peat deposits in Quebec, Canada (Dever et al, 1984), Dartmoor, UK (Charman et al, 1999), Lithuania (Mažeika et al, 2009), and Minnesota, USA (Siegel et al, 2001). From the preservation of seasonal δ 18 O and δ 2 H values, Aravena and Warner (1992) estimated that the water from the upper ∼ 0.1 m of peat from Ontario, Canada, was < 1 year old.…”
Section: Transit Times In Upland Peatmentioning
confidence: 99%
“…The 3 H activity in the groundwater of the studied area can be related to 3 H variation in atmospheric precipitation and in surface water as groundwater recharge sources. The mean annual 3 H activity in atmospheric precipitation in the last 10 yr is about 10 TU (Mažeika et al 2009). Significantly higher 3 H activity (an average of 40-50 TU and maximum of 204 ±11 TU in 2003) can be observed in the water of Lake Druksiai and boggy areas on the lake shores that are related with pathways of liquid releases from the INPP in normal operation.…”
Section: Resultsmentioning
confidence: 98%
“…The 3 H concentration in monthly precipitation records since 1952 is based on correlation of the Global Network of Isotopes in Precipitation (GNIP Vienna Hohe Warte station) data with the 3 H measurements in month precipitation in east Lithuania since 1999 (Mažeika et al 2009). From the correlated monthly record of 3 H concentrations in precipitation, the 3 H input function was set to = 0.66, where  =  s / w and represents the ratio of infiltration coefficients in summer ( s ) and winter ( w ) months of each year.…”
Section: Groundwater Age and Mean Residence Timementioning
confidence: 99%
“…To understand what hydrogen and oxygen isotopes represent, we have to understand the hydrology of peat composed of Sphagnum accumulates. Mažeika et al (2009) investigated water circulation in peat bogs, simply applying distillation to peat bogs, and reported that downward water flow in bogs is significant based on 3 H vertical profiles. Although water in hyaline cells ought to comprise a significant portion in peats, the role of hyaline cell water is unclear.…”
Section: Introductionmentioning
confidence: 99%